Influência do tetraétil-ortosilicato e etilenoglicol no polimorfismo e morfologia de CACO3 em matrizes cimentícias na idade inicial de hidratação - Bartley, Bertilia Lauralee (2020)
The polymorphism, stabilization, and morphology of calcium carbonate (CaCO3) in pure systems and biomineralization is a widely discussed topic. In the last two decades, studies in cementitious matrices have shown that this compound has potential application as an autogenous self-repairing agent for concrete micro-cracks. However, its behavior as a self-repair agent is not yet fully elucidated, particularly in the presence of additives. And one of the aspects to be considered is the correlation between morphology and self-repair capacity. Therefore, it is necessary to find the conditions for the control and stabilization of the different CaCO3 polymorphs in the presence of additives in cementitious matrix. In this context, the influence of ethylene glycol (EG) and tetraethyl-orthosilicate (TEOS) were studied as self-healing agents, and on the formation and polymorphism of CaCO3 in the cementitious matrix at initial curing ages by SEM, XRD, TGA and FTIR. The additives were incorporated into the mixing medium of cement paste in a solution of deionized water and 50% viii ethanol(w/w). Specimens were molded for 24 h at 23°C, then cured for an additional 24 h at 23 & 75°C. Results show that TEOS and EG play a significant role in mediating the morphological habit of CaCO3 crystals. Vaterite is predominant in both systems throughout curing at 23°C; TEOS promotes dendritic morphologies composed of elongated thin plates that diverge radially, while EG promotes the compact 'cauliflower' morphologies, composed of acicular crystals. At 75°C, aragonite predominates the microstructure of the EG system, from the self-assembly of pseudohexagonal mesocrystals to the spherulitic growth of these crystals to ‘sea-urchin’ morphologies. After 24h of hydrothermal curing, CaCO3 polymorphs are not prevalent in the TEOS system, yet the consumption of portlandite to form fibril C-S-H is observed. The results show that the EG promotes a greater precipitation and diversity of CaCO3 polymorphs, indicating better stabilization of the phases, under the studied time and temperature conditions. While TEOS shows favorable influence on the continued formation of fibril C-S-H, from the consumption of portlandite, which intertwines and densifies the microstructure, demonstrating promising characteristics of selfhealing in the system via formation of C-S-H.